Qur’anic Memorization as Lived Religious Practice Among Children with Special Needs: A Living Qur’an Study of Tajdied Method Mumtaz School - Muhammad Irza Tsaquf Ali; Ikhwanul Mukminin; Abdul Qudus Al Faruq; Selena Chayka Salsabilla (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2026)
Inclusive Qur’anic education demands pedagogical approaches that respond to the diverse cognitive, emotional, and sensory characteristics of children with special needs, as conventional memorization models often emphasize technical accuracy while overlooking how the Qur’an is experienced and embodied in daily learning. This study examines Qur’anic memorization as a lived religious practice through the implementation of the Tajdied Method at Mumtaz Elementary School, Sidoarjo. Using a qualitative case study design, data were collected through classroom observations, in-depth interviews with Qur’an teachers, inclusive facilitators, and students, as well as institutional documentation. The data were analyzed thematically within a living Qur’an framework. The findings reveal that the Tajdied Method—integrating rhythmic movement, melodic recitation, and mnemonic reinforcement—encourages affective involvement and embodied engagement with the Qur’an. Memorization is thus positioned not merely as a cognitive achievement but as an emotionally mediated and socially situated religious experience. Learning outcomes varied, influenced by attention span, sensory sensitivity, emotional regulation, and teacher–student interaction. This study contributes to living Qur’an scholarship by reframing Qur’anic memorization among children with special needs as an experiential, contextual, and socially embedded religious practice.